DUKUNGAN SUAMI DALAM MENINGKATKAN SELF EFFICACY PADA IBU HAMIL YANG BERESIKO TINGGI - Risti Linta Chumaira; Nurya Kumalasari; Meity Mulya Susanti; Sutiyono; Mika Agustiana (Jurnal Pengabdian kepada Masyarakat Cahaya Negeriku, 2025)
Background: High-risk pregnancy poses threats to the health and life of both mother and baby. In Indonesia, maternal mortality remains high due to bleeding, hypertension, and infections. Psychological issues such as anxiety and low self-efficacy worsen outcomes. Husband’s support is crucial in improving maternal self-efficacy. Purpose: This community service aimed to educate high-risk pregnant women and their husbands on the importance of husband’s support to enhance maternal self-efficacy. Method: Conducted in Menduran Village with 10 participants (pregnant women and their husbands), the program involved problem identification, planning, team formation, and implementation. Education was delivered through lectures using maternal health books, leaflets, and audio aids. A 15-question pre-test and post-test assessed knowledge improvement. Results: Before the intervention, 60% had poor knowledge. Afterward, 90% showed good knowledge, indicating significant improvement. Conclusion: Husband’s support significantly enhances self-efficacy in high-risk pregnant women, aiding their physical and psychological adaptation during pregnancy. Family involvement, especially from the husband, is key to ensuring safe pregnancy outcomes.